Urban dwellers’ hazard awareness and its implications on Disaster Risk Reduction and Management towards climate change adaptation and urban resilience - Rosel, Minerva C.; Malaque III, Isidoro R. (2023)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/9536/8416
Keywords: Disaster Risk Reduction and Management (DRRM); Sustainable development; Urban planning